Citations from Theodor Lepner’s “Prūsų lietuvis” in Simonas Daukantas work “Būdas senovės lietuvių, kalnėnų ir žemaičių” - Bončkutė, Roma (Knygotyra, 2018)
[full article and abstract in Lithuanian; abstract in English]This article analyses the citations from the ethnographic study “Der Preuſche Littauer” (1744; later cited as PL) by the Prussian priest Theodor Lepner which appear in the work of Simonas Daukantas (1793–1864) “BUDĄ Senowęs–Lëtuwiû Kalnienû ir Ƶámajtiû ĩszraszę […] Jokyb’s Łaukys” (later cited as “Būdas”).The object of this article is the 31 references to PL in S. Daukantas’s “Būdas”. Looking at the previous scholarly research on “Būdas” and its sources along with the subsequent questions they pose, this article formulates a goal to research the methods with which PL source citations were presented in Būdas. This goal was completed by setting and meeting the following tasks: 1) to determine the importance of PL as a source for S. Daukantas’s research into the history of Lithuanian culture; 2) to exhibit S. Daukantas’s use of citations instead of research into firsthand sources and 3) to discuss the reliability and fidelity with which these citations and references are presented. In order to analyze the text, this article employs the following methods: comparative analysis; textology; intertextuality.By examining these citations and references, it was discovered that Daukantas encountered this text indirectly sometime between 1818 and 1825 when he was writing his first history “Darbay senuju Lituwiu yr Zemaycziu” (around 1822–1825). This article determines that Daukantas found these quotations from Lepner’s book in Martin L. Rhesa’s addenddum (“Anmerkungen”) of “Das Jahr in vier Geſängen” (1818). Daukantas used this addenddum to recite Lepner in his second historical work “Istorija Žemaitiška” (1831–1834). Later he found the fragments of Lepner’s “Der Preuſche Littauer” in one of his most important sources – Johannes Voigt’s “Geschichte Preußens” (Bd. 1, 1827). Daukantas had used this book by Voigt to recite an older source several times before. This article demonstrates that Daukantas used Voigt’s book to recite the fragments of Matthäus Prätorius’s (c.1635–c.1704) „Deliciae Prussicae, oder Preussische Schaubühne“ manuscript. It somewhat changes the previous opinion about Daukantas’s comprehensive historiographical knowledge, diminishing his image as a researcher familiar with many of the old or primary sources.This article concludes that Daukantas read “Der Preuſche Littauer” around 1836 or 1837 when he was already residing in Saint Petersburg.The quotes from “Der Preuſche Littauer” contained in Daukantas’s Būdas are grouped according to the nature of their textual integration. “Būdas” contains 31 quotes and references from “Der Preuſche Littauer”. None of the citations from “Der Preuſche Littauer” that Daukantas had used were distinguished with quotation marks or a different font, and they could only be recognized from their content. Quite often, Daukantas quotes “Der Preuſche Littauer” in several sentences without marking the beginning of the quotation and giving the indication only at the endof the sentence using small letters with brackets, eg.: a), b), c), e), d). Daukantas quite accurately reproduces the text of “Der Preuſche Littauer” and gives the exact reference only 17 times out of31. 8 times his references are incorrect: both in terms of the content and the page numbers. 6 referencescontain accurate content cited from “Der Preuſche Littauer” but give erroneous page and section numbers. Daukantas was the first of 19th century Lithuanian writers who had his unique writing style and historical perspective. This original prism determined the use of indirect citations of “Der Preuſche Littauer”. I determined that because no firsthand Lithuanian historical sources existed Daukantas was forced to use foreign sources such as PL which marginalized Lithuanians as members of an ethnic minority and strange satyre-worthy objects thus requiring for him to engage in historical revisionism by factual reconstruction and reinterpretation from a Lithuanian perspective. He used these secondhand sources to deobjectify Lithuanians and make them into subjects and agents of their own history and destiny by describing their past and character through their eyes. This historical revisionism determined the way Daukantas cited and referenced T. Lepner’s text as a source. Daukantas avoided marking citations in quotation marks since they would then have to be translated as close to the original as possible which would have impeded with his historical vision. To make his narration and perspective congruous with his values and style he edited not only the language of the citations from “Der Preuſche Littauer” but also their content. Most of the information obtained from “Der Preuſche Littauer” was paraphrased, processed, and rewritten in such a way as to incorporate the new text into Daukantas’s own style and ideas. However, it may also be that Daukantas sometimes misquoted the text because he did not understand how the item described in German could look and how he should describe it in Lithuanian. Daukantas often sacrificed the fidelity to the text of “Der Preuſche Littauer” in favour of emotional and expressive speech.Translated from the Lithuanian by Ieva Poškutė, BA (Hons) in Film and Literature at University of Warwick.